Managerial ability impact on lending and bank credit quality: SFA approach - Fikri Asyrafi; Henny Setyo Lestari (International Ecsis Association, 2022)
The banking sector is one of the vital sectors in connection with its role in distributing funds to the public through lending. This makes many researchers search for variables that affect lending by banks. Still, previous studies have focused more on definitive factors and seem to ignore intangible factors such as bank managerial ability. This study examines the effect of managerial ability and bank-specific factors on bank lending and credit quality. The estimation of managerial ability uses a stochastic frontier analysis approach, while panel regression with fixed effects is used to analyze the research model. This study uses a sample of banks registered on IDX during 2010 – 2021. The results show that managerial ability significantly positively affects lending and bank credit quality. Bank-specific factors such as bank size, workforce, and capital also significantly affect lending and bank credit quality. At the same time, this study did not find the effect of deposit growth on the dependent variable of lending and bank credit quality. The results of this study have implications that banks can expand and improve credit quality by increasing the ability of bank managers.